Geographic and Specialty Distribution of US Physicians Trained to Treat Opioid Use Disorder - Rosenblatt, Roger A.; Andrilla, C. Holly A.; Catlin, Mary; Larson, Eric H. (Annals of family medicine, 2015)
The United States is experiencing an epidemic of opioid-related deaths driven by excessive prescribing of opioids, misuse of prescription drugs, and increased use of heroin. Buprenorphine-naloxone is an effective treatment for opioid use disorder and can be provided in office-based settings, but this treatment is unavailable to many patients who could benefit. We sought to describe the geographic distribution and specialties of physicians obtaining waivers from the Drug Enforcement Administration (DEA) to prescribe buprenorphine-naloxone to treat opioid use disorder and to identify potential shortages of physicians. We linked physicians authorized to prescribe buprenorphine on the July 2012 DEA Drug Addiction Treatment Act (DATA) Waived Physician List to the American Medical Association Physician Masterfile to determine their age, specialty, rural-urban status, and location. We then mapped the location of these physicians and determined their supply for all US counties. Sixteen percent of psychiatrists had received a DEA DATA waiver (41.6% of all physicians with waivers) but practiced primarily in urban areas. Only 3.0% of primary care physicians, the largest group of physicians in rural America, had received waivers. Most US counties therefore had no physicians who had obtained waivers to prescribe buprenorphine-naloxone, resulting in more than 30 million persons who were living in counties without access to buprenorphine treatment. In the United States opioid use and related unintentional lethal overdoses continue to rise, particularly in rural areas. Increasing access to office-based treatment of opioid use disorder—particularly in rural America—is a promising strategy to address rising rates of opioid use disorder and unintentional lethal overdoses.